Dissipative control for singular time-delay system with actuator saturation via state feedback and output feedback - Fu, Lei; Ma, Yuechao (International journal of systems science, 2018)
This paper is devoted to the problem of dissipative control for a class of singular time-delay systems with actuator saturation via state feedback and output feedback. First, by tuning the Wirtinger-based integral and the double integral inequality, a sufficient condition is derived to guarantee that the singular time-delay system is regular, impulse free, asymptotically stable and strictly (Q,S,R)-dissipative. Then, based on the derived condition, and applying linear matrix inequality techniques, the dissipative state feedback and output feedback controller are synthesised. Moreover, the maximal estimate of the domain of attraction is proposed by an optimisation problem. Finally, some simulation examples are provided to verify the effectiveness of the obtained theoretic results.